EXPLORING THE APPLICABILITY OF FORENSIC AUDITING TECHNIQUES IN THE DETECTION OF TAX EVASION IN FIRS HEAD QUARTER ABUJA - ADEBAYO, ADELANI AHMAD; YAKASAI, IBRAHIM AMINU; ENE, JOSEPHINE C. (Kashere Journal of Management Sciences, 2025)
This research examined the use of forensic auditing methods for detecting tax evasion at the Federal Inland Revenue Service (FIRS) headquarters in Abuja. The research evaluated forensic auditing methods including ratio analysis, data mining and data analytics to determine their individual impact on detecting fraudulent tax activities. The assessment evaluated these techniques based on their individual impact on tax evasion detection rate, ability to uncover unreported income and their effect on taxpayer compliance respectively. The study employed a descriptive survey method to obtain data directly from FIRS personnel through a standardized questionnaire. The research demonstrates that forensic auditing techniques especially data mining prove effective for tax evasion detection at FIRS Headquarters in Abuja. Data analytics had a significant effect on taxpayer’s compliance. The study used ratio analysis as a forensic auditing tool however it does not have a statistically significant effect on the detection of tax evasion. Overall, the study discloses that FIRS is ready to employ forensic auditing techniques. This research indicates that forensic methods particularly data mining and data analytics when applied practically will boost compliance and decrease revenue losses.